2023
DOI: 10.1094/pdis-11-22-2628-sc
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Ralstonia pseudosolanacearum (Phylotype I) in Aquatic Environments in the Netherlands

Abstract: Ralstonia pseudosolanacearum, a European Union quarantine organism, was until recently absent in the aquatic environments and outdoor cultivation systems inside the region. This bacterium was only sporadically reported in restricted greenhouse cultivation systems in some EU countries. In this paper we report the first findings of R. pseudosolanacearum (phylotype I) in surface water in two distinct geographic locations in the Netherlands in 2020. In 2021, the population of Ralstonia pseudosolanacearum in surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…A study by French et al ( 70 ) found that in a river environment, urban development and farming had significant impacts on the virus community present in the water. In our study, the influence of land usage and terrestrial water input may explain the detection of phages associated with prokaryotic hosts that cause plant diseases such as the Ralstonia phage, which was identified in high abundance at Cox’s Bazar ( 71 ). Furthermore, anthropogenic water inputs to a marine environment typically add nutrients such as phosphorus and nitrogen, which are often thought of as limiting nutrients for photosynthetic organisms in the photic zone ( 72 ).…”
Section: Discussionmentioning
confidence: 80%
“…A study by French et al ( 70 ) found that in a river environment, urban development and farming had significant impacts on the virus community present in the water. In our study, the influence of land usage and terrestrial water input may explain the detection of phages associated with prokaryotic hosts that cause plant diseases such as the Ralstonia phage, which was identified in high abundance at Cox’s Bazar ( 71 ). Furthermore, anthropogenic water inputs to a marine environment typically add nutrients such as phosphorus and nitrogen, which are often thought of as limiting nutrients for photosynthetic organisms in the photic zone ( 72 ).…”
Section: Discussionmentioning
confidence: 80%
“…Although R. solanacearum phy II is already present in surface water in certain areas in the Netherlands, it could be introduced in waterways where it is not yet present, thereby forming a risk for crops grown near these waterways. Recently, indications for a similar occurrence for phylotype I were found (Vogelaar et al, 2023). R. pseudosolanacearum phy I, posing a potential threat to potato production (Overeem et al, 2023), has recently been found in surface water in the Netherlands at a restricted number of locations, and sequence analysis showed that the R. pseudosolanacearum phy I isolates found in surface water and bittersweet are closely related to the R. pseudosolanacearum phy I isolates that were found in rose before (Vogelaar et al, 2023), suggesting a potential link between the two.…”
Section: Discussionmentioning
confidence: 80%
“…Ralstonia phage was also uniquely dominant in Cox's Bazar and suggest runoff input into this site since the bacteria of the genera Ralstonia are usually found in freshwater and soil environments often as pathogens for crops. The presence of this phage species could be indicative of runoff and freshwater inputs near the BoB (Vogelaar et al, 2023). Cyanophages were also found in much higher abundance at Cox's Bazar, but it is unclear how this enrichment relates to terrestrial proximity compared to Saint Martin since cyanophages are present in both freshwater and marine habitats (Xia et al, 2013).…”
Section: Diversity Abundance and Functional Potential Of Prokaryotic ...mentioning
confidence: 99%